2009
DOI: 10.1159/000204961
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Studies of an Impetigo Bullosa Epidemic in Full-Term Infants

Abstract: Background: Carriers ofStaphylococcus aureus strains can be the source of epidemic infection for patients. Objectives: A molecular epidemiological analysis of an impetigo bullosa outbreak in a neonatal ward was performed in order to determine a potential source of the infection and possible routes of subsequent spreading of the epidemic strain. Methods: The genetic relatedness of S. aureus strains isolated from 6 neonates with epidermal lesions and from 21 staff members was verified by the pulsed field gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…The Tzanck smear is also an easy method to illustrate acantholysis [16] . Determining the exfoliative toxin produced by the S. aureus can be helpful in epidemiological studies during outbreaks on neonatal wards but is not necessary for the diagnosis SSSS [17] . To prevent out- Seven cases with SSSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tzanck smear is also an easy method to illustrate acantholysis [16] . Determining the exfoliative toxin produced by the S. aureus can be helpful in epidemiological studies during outbreaks on neonatal wards but is not necessary for the diagnosis SSSS [17] . To prevent out- Seven cases with SSSS.…”
Section: Discussionmentioning
confidence: 99%
“…Case 5 published before [11]. [17] . Recently, Blyth et al [3] described the diagnosis and treatment in 4 older children with SSSS.…”
Section: Discussionmentioning
confidence: 99%
“…In the neonatal period, S. aureus has been associated with a variety of disorders of varying degrees of severity, such as nosocomial outbreaks of neonatal impetigo 1, omphalitis 2, arthritis and osteomyelitis 3, late neonatal nosocomial or community-acquired sepsis 4,5, and sudden infant death syndrome 6. A systematic review of the literature, with 19 studies and more than 4000 blood culture isolates identified that the most common causes of neonatal bacteremia were S taphylococcus aureus, Escherichia coli and Klebsiella spp.…”
Section: Introductionmentioning
confidence: 99%
“…No período neonatal, o S. aureus tem sido associado às infecções de gravidade variável, como surtos nosocomiais de impetigo neonatal (JURSA-KULESZA et al, 2009), onfalite (MIR et al, 2011), artrite e osteomielite (BERBERIAN et al, 2010;MONTGOMERY et al, 2013), sepse neonatal tardia, adquirida em hospital ou oriunda da comunidade (GANATRA e ZAIDI, 2010;DOWNIE et al, 2013;COOMBS et al, 2013) e à síndrome da morte súbita infantil (HARRISON et al, 2008;WEBER et al, 2011).…”
Section: Introdução 1 Introduçãounclassified
“…Among the bacteria that colonize mucous membranes of pregnant women and, soon after birth, their newborns (NB), is Staphylococcus aureus (S. aureus). In the neonatal period, S. aureus has been associated with infections of variable severity, as nosocomial outbreaks of neonatal impetigo [1], omphalitis [2], arthritis and osteomyelitis [3], late neonatal sepsis nosocomial or community-acquired [4][5][6], and the sudden infant death syndrome [7,8].…”
Section: Introductionmentioning
confidence: 99%